Transforming Education: Optimizing Learning Environments through the Fusion of Signal Processing and IOT - Sri Harsha Grandhi (AG Volumes, 2024)
In the Indian context, the New Education Policy (NEP) of 2020 is an innovative blueprint that foresees a fundamental transformation of the educational environment centred around technology. This paper investigates the symbiotic connection between technological integration as well as the NEP 2020, concentrating on IoT and signal processing. By adopting a learner-centric stance, the NEP 2020 considers the changing demands of twenty-first century. The objective is to establish an educational environment that is technologically advanced, flexible, and inclusive, with the capacity to accommodate diverse learning preferences. Furthermore, it promotes the early cultivation of critical thinking, creativity, as well as problem-solving skills.